2016
DOI: 10.1089/omi.2015.0118
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing L-Menthol for Systems Medicine and Cancer Therapeutics? L-Menthol Induces Apoptosis through Caspase 10 and by Suppressing HSP90

Abstract: The objective of the present study was to repurpose L-menthol, which is frequently used in oral health and topical formulations, for cancer therapeutics. In this article, we argue that monoterpenes such as L-menthol might offer veritable potentials in systems medicine, for example, as cheaper anti-cancer compounds. Other monoterpenes such as limonene, perillyl alcohol, and geraniol have been shown to induce apoptosis in various cancer cell lines, but their mechanisms of action are yet to be completely elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 125 publications
0
6
0
Order By: Relevance
“…Menthol is another important compound of ZEO. Various studies have shown that menthol activates caspases 3 and 7 through caspase 10 affecting HSP90, followed by apoptosis [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Menthol is another important compound of ZEO. Various studies have shown that menthol activates caspases 3 and 7 through caspase 10 affecting HSP90, followed by apoptosis [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…l -Menthol, one of the main components of Mentha species, has multiple applications in traditional medicine. Faridi et al observed that it modulated tubulin polymerization, induced apoptosis and also suppresses the expression of HSP90 [ 161 ]. In their proposed model, the latter authors suggested that l -menthol provoked apoptosis directly via caspase 10 activation and also activated caspase 9 which indirectly triggered caspase 3 and mitochondrial cell death [ 161 ].…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%
“…Faridi et al observed that it modulated tubulin polymerization, induced apoptosis and also suppresses the expression of HSP90 [ 161 ]. In their proposed model, the latter authors suggested that l -menthol provoked apoptosis directly via caspase 10 activation and also activated caspase 9 which indirectly triggered caspase 3 and mitochondrial cell death [ 161 ]. Perillyl alcohol is a monoterpene isolated from lavendin, peppermint, spearmint and some other plants [ 162 ], and several studies showed that this compound could inhibit tumor progression.…”
Section: Properties Of the Mentha Genusmentioning
confidence: 99%
“…One recent example is that of L-menthol, a naturally occurring cyclic monoterpene obtained from Mentha arvensis (Lamiaceae) that has been traditionally used in oral hygiene products, confectionery, cosmetics and as a flavouring agent. An omics approach indicated that L-menthol modulates tubulin polymerization and apoptosis to inhibit human epithelial colorectal adenocarcinoma cell proliferation (Faridi et al, 2011;2016). Similarly, Puerarin (Pue), belonging to the isoflavone glycoside group and derived from Pueraria lobata, P. thomsonii and P. tuberosa was recommended by the Chinese Health Ministry for treating various ailments in 1993, but later it was found to possess anticancer activity too by virtue of it being an inducer of apoptosis (Ahmad et al, 2020).…”
Section: Biosynthesis Of Novel Phytomolecules and Novel Activities Fo...mentioning
confidence: 99%